'Following the word of God': Empirical insights into managerial perceptions on spirituality, culture and health. (June 2014) - Mayer, Claude-Hélène; Viviers, Rian
Abstract This article focuses on managers in a selected South African organization and the connections they draw between mental health, culture and spirituality within the workplace. The aim is to gain a deeper understanding of the interrelationships in this complex and growing scientific discourse and to respond to the research question of how mental health, culture and spirituality are interrelated from a managerial perspective. The study follows an inductive single case study approach within the phenomenological paradigm. Qualitative research methods using in-depth interviews and observation were used. The sample comprised 27 managers within the international South African automotive organization. The findings show that not only culture, but also spirituality and religion in particular, influence mental health and well-being of managers at work. Conclusions are drawn and recommendations made.